2010
DOI: 10.1002/cpp.729
|View full text |Cite
|
Sign up to set email alerts
|

Auditory hallucinations: a review of assessment tools

Abstract: Auditory hallucinations are a common and troubling symptom in psychotic disorders. We aimed to identify measures that could be used by clinicians and researchers to assess the experience of auditory hallucinations. A literature review was conducted to identify auditory hallucination measures that were developed since the last such review in 1998. We identified 10 tools: eight self-report measures and two clinical interviews. The scales measured diverse constructs and are divided into four categories for review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 67 publications
(99 reference statements)
0
41
0
Order By: Relevance
“…Considering the above and the conclusion of Ratcliff et al (2011) that the PSYRATS (Haddock et al 1999) might be refined and validated further, we consider that the AVHRS meets these recommendations and will be useful in identifying treatment targets beyond diagnosis (Nasrallah et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Considering the above and the conclusion of Ratcliff et al (2011) that the PSYRATS (Haddock et al 1999) might be refined and validated further, we consider that the AVHRS meets these recommendations and will be useful in identifying treatment targets beyond diagnosis (Nasrallah et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, McEnteggart and colleagues used the IRAP to investigate whether fear of voices would decrease after a hearing voices simulation in a group of non-voice hearers, but interestingly it was found that fear increased. Consistent with the psychosis literature generally, all other studies of voice hearing have relied largely on explicit measures (for both clinical and research purposes, see Kim et al, 2010;Ratcliff, Farhall, & Shawyer, 2010).…”
Section: Hearing Voices Researchmentioning
confidence: 92%
“…These measures are widely used in the assessment of voice hearing (see Ratcliff, Farhall, & Shawyer, 2010), and the aim of their inclusion was to examine the predictive validity of the IRAP data in this domain, and not in the diagnosis of a psychotic disorder. In particular, the CAPE is used extensively to assess the presence of hearing voices and it was used for this purpose here.…”
Section: Methodsmentioning
confidence: 99%
“…These methods are presented in two reviews of AH assessment tools (Frederick & Killeen, 1998;Ratcliff, Farhall, & Shawyer, 2011).…”
Section: Background Review Of Existing Instruments To Assess Auditorymentioning
confidence: 99%
“…The Ratcliff et al (2011) review explored 10 instruments developed to assess AH between 1998 and 2009. Two were structured interviews, and eight were self-report.…”
Section: Background Review Of Existing Instruments To Assess Auditorymentioning
confidence: 99%